Flushed away [videorecording (DVD)] - Clement, Dick; La Frenais, Ian; Lloyd, Christopher, 1960-; Keenan, Joe, 1958-; Davies, William (Screenwriter); Jackman, Hugh; Winslet, Kate; McKellen, Ian; Reno, Jean, 1948-; Nighy, Bill, 1949-; Serkis, Andy; Richie, Shane, 1964-; et al. (DreamWorks Animation SKG Home Entertainment, 2007)
Roddy is a decidedly upper-crust "society mouse" who lives the life of a pampered pet in a posh Kensington flat. When a sewer rat named Sid comes out of the sink, he decides he has hit the jackpot. Roddy schemes to rid himself of Sid by luring him into the "whirlpool." Sid may be an ignorant slob, but he's no fool, but it is Roddy who winds up being flushed away into the bustling sewer world of Ratropolis. There Roddy meets Rita, an enterprising scavenger who works the sewers in the Jammy Dodger, her faithful boat. Roddy immediately wants out, or rather, up. Trouble comes in the form of the villainous Toad -- who royally despises all rodents. The Toad dispatches his two hapless hench-rats, Spike and Whitey, to get the job done. When they fail, the Toad has no choice but to send to France for his cousin, Le Frog, the dreaded mercenary.